2020
DOI: 10.1007/s10654-020-00650-3
|View full text |Cite
|
Sign up to set email alerts
|

Global, regional and time-trend prevalence of central obesity: a systematic review and meta-analysis of 13.2 million subjects

Abstract: We aimed to examine the global prevalences of central obesity according to age, sex, race, place of residence, geographical region, national income level, and the definitions of central obesity. MEDLINE and Embase were searched. Studies with sample size of ≥ 500 and investigated individuals aged ≥ 15 years were included. Metaprop (a Stata command) was adopted to conduct a meta-analysis of prevalence, and the Freeman-Tukey Double Arcsine Transformation was used to stabilize the variances. A random-effects model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
120
1
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(171 citation statements)
references
References 51 publications
5
120
1
8
Order By: Relevance
“…Indeed, using a cut-off point for WC of ≥94 cm for men and ≥80 cm for women, a recent meta-analysis by Wong et al . [28] reported that the global prevalence of abdominal obesity was 41.5% [95% CI: 39.9–43.2%]. This prevalence is higher than those reported in our study using the same WC cut-off point.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Indeed, using a cut-off point for WC of ≥94 cm for men and ≥80 cm for women, a recent meta-analysis by Wong et al . [28] reported that the global prevalence of abdominal obesity was 41.5% [95% CI: 39.9–43.2%]. This prevalence is higher than those reported in our study using the same WC cut-off point.…”
Section: Discussioncontrasting
confidence: 67%
“…Using the WHO definition, Wong et al . [28] reported that nearly half (41.5%) of the global adult population was abdominally obese and that this prevalence is rising worldwide, including in low- and middle-income countries in SSA. However, there is a paucity of data on abdominal obesity in SSA as previously highlighted by Wong et al [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, despite exhibiting a similar mean body mass index (BMI), postmenopausal women have a larger WC [ 15 ]. While both genders experience somatic changes with aging, in women they particularly affect the WC and waist-to-hip ratio (WHR) [ 33 , 38 ]. Interestingly, both visceral and subcutaneous adipocytes express estrogen and androgen receptors such as ER-α, a regulator of adipocyte activity and fat distribution responsible for these gender differences and hyperandrogenism in postmenopausal women [ 15 , 39 ].…”
Section: Beer Consumption Related To Health and Disease In Womenmentioning
confidence: 99%
“…According to a recent estimation on worldwide obesity from the WHO in 2016, the global prevalence of obesity has nearly tripled since 1975 [ 46 ]. Another study on the global burden of central obesity also found that the prevalence increased from 16.3% to 33.9% during 1985–2014 [ 47 ]. The past two decades also witnessed a marked increase in the prevalence of metabolic syndrome (from 22.8% to 27.0%) [ 48 ].…”
Section: Discussionmentioning
confidence: 99%